Transitioning to Responsible Consumption and Production - McNeill, Lisa (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Responsible Consumption and Production, the twelfth UN Sustainable Development Goal (SDG 12), calls for significant change in how we view both production and consumption norms. It is predicted that, at the current rate of population growth and consumption, the natural resources needed to sustain current lifestyles would require the equivalent of almost three planets by 2050. It is clear that change is required, involving action from everyone from the producer to the final consumer. Since sustainable consumption aims for world citizens to 'do better with less', all aspects of this change must be carefully considered with regard to critical ecological and social models that transform all production and consumption practices that are recognised as negative. Transitioning to Responsible Consumption and Production focuses on the transition to responsible production and consumption, and models that aid that transition. It offers a multi-disciplinary, multi-stakeholder conversation on this issue, with a focus on the intersection between encouraging and enhancing sustainable production processes, and enacting behaviour change and socially oriented decision-making by consumers.